Tuckman and Tom Edison model of team developments applied by STKIP Weetebula team for implementation of SPS (Seminar-Practice-School). - kii Yape Wilhelmus (Jurnal Edukasi Sumba (JES), 2019)
The first part of this paper explains the team development of Tuckmans and Edisons models including the differences between these two models. The paper starts with Tuckmans model, which is known as a traditional model of team development. In 1965, Tuckman stated that an organization that would like to accomplish its goal through teamwork followed four main stages of team development, which he named as forming, storming, norming and performing. In 1977, Tuckman and Mary Ann Jansen added a fifth stage named adjourning. In 2011, Edison assessed that Tuckmans model could be further developed. Tuckman's traditional model is needed for understanding a team's basic functional stages, but his model needs to be expanded for greater understanding of team development, especially during a team's dysfunctional phases. This articleidentifies one phase of team development that complements the classic five phases developed by Tuckman. To reach the objectives of a project team, it is important to understand and review thedysfunctional phases (conforming and deforming) that a team encounters so that appropriate corrective actions can be taken to aid a team in becoming high-performing.Based on the analysis of those two models, this article explains the integration of these models when applied by STKIP Weetebula team when working on improving the learning process. The main goal of the team is developing and implementing a new subject on the curriculum of all study programs of STKIP Weetebula, Sumba, Indonesia. The new subject is named as SPS (Seminar-Praktek-Sekolah/Seminar-Practice-Schools). The team has started to work from August 2016 to August 2017. The team has designed an action planning for SPS and has implemented it in March 2017. The team consists of 2 pedagogical advisors/facilitator from Germany, 6 STKIP lecturers, and 1 staff member. This article shows how SPS team works to reach its goals by integration of team development stages of Tuckmans and Edisons models.